2018
DOI: 10.3390/condmat4010002
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Superconductivity in Doped Bi2Se3 Topological Superconductors

Abstract: Nematic superconductivity is a novel class of superconductivity characterized by spontaneous rotational-symmetry breaking in the superconducting gap amplitude and/or Cooper-pair spins with respect to the underlying lattice symmetry. Doped Bi 2 Se 3 superconductors, such as Cu x Bi 2 Se 3 , Sr x Bi 2 Se 3 , and Nb x Bi 2 Se 3 , are considered as candidates for nematic superconductors, in addition to the anticipated topological superconductivity. Recently, various bulk probes, such as nuclear magnetic resonance,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 110 publications
4
63
0
Order By: Relevance
“…In addition, numerous experiments have shown that the superconducting state is accompanied by a spontaneous breaking of rotational symmetry with a pronounced twofold anisotropy within the Bi 2 Se 3 basal plane [15][16][17][18][19][20][21][22] ; see Ref. 23 for a recent review. The twofold symmetry can be observed in field-angle resolved experiments where a magnetic field is rotated in the plane with respect to the crystalline axes and the corresponding physical quantity (e.g., spin susceptibility, specific heat, magneto-resistance, upper critical field, magnetization, magnetic torque) is represented as a function of angle [15][16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…In addition, numerous experiments have shown that the superconducting state is accompanied by a spontaneous breaking of rotational symmetry with a pronounced twofold anisotropy within the Bi 2 Se 3 basal plane [15][16][17][18][19][20][21][22] ; see Ref. 23 for a recent review. The twofold symmetry can be observed in field-angle resolved experiments where a magnetic field is rotated in the plane with respect to the crystalline axes and the corresponding physical quantity (e.g., spin susceptibility, specific heat, magneto-resistance, upper critical field, magnetization, magnetic torque) is represented as a function of angle [15][16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…After the initial observations, nematic SC behavior has been consistently observed by using various probes such as transport, thermodynamic, and microscopic techniques [10][11][12][13][14][15][16][17][18] , as reviewed in ref. 19 . We comment here that these doped Bi 2 Se 3 nematic superconductors are quite distinct from iron pnictide superconductors, where nematicity occurs in the normal state as a consequence of orbital ordering and superconductivity eventually occurs at much lower temperatures 4 .…”
mentioning
confidence: 99%
“…However, the specific heat measurement [20] suggests the pairing gap is maximal along y in the momentum space, hence is consistent with the D y 4 pairing instead. More experimental results are summarized nicely in [38], showing almost equal popularities of D x 4 and D y 4 pairing. Such a variety of the probed d-vectors implies the d-vector may be fragile and therefore dependent on material details, as demonstrated by our results.…”
Section: Discussionmentioning
confidence: 84%